Pembelajaran Sekar Rare dalam Tarian Janger Sakral Seka Teruna Teruni Banjar Pegok Desa Adat Sesetan - Darma Putra, Made Fandy (Metta : Jurnal Ilmu Multidisiplin, 2021)
Traditional literature is a work related to beautiful script and language. Balinese Purwa literary works are a part of Balinese literature which is usually called traditional literature. The existence of literature in Bali to this day is still preserved and developed by the Balinese people and has become one of the tourist attractions, this is what makes the Balinese people continue to inherit ancestral culture which contains values, closely related to the life of the people in Bali, one of which is gegendingan . The rare sekar discussed in this research is Gending Jangér. One of the groups or sekaa janger that still exists today is the sekaa janger in the traditional village of Sesetan, namely the janger Seka Teruna-teruni Widya Bhakti Banjar Pegok in Denpasar City. The aim of this research is to find out the pieces and the meaning contained in the Janger Dance as well as how to teach the Janger pieces to Banjar Pegok janger dancers. In this research, researchers used three theories, namely the first, researchers used structuralism theory, the second, meaning theory, and the third, behaviorist theory. Data collection methods from research are, observation, interviews, documentation and literature. The results of the research obtained in the Janger dance gending are that there are five gending structures, namely, pengaksama, pepeson, tetamburan, pecet, pekaad. The meaning contained in Janger's gending is that there are four meanings, religious, social, cultural preservation and entertainment. In teaching Janger gending, three methods are used, namely, direct, reading and audio-lingual methods. The participation of community leaders is very necessary to encourage and guide the younger generation to continue preserving Janger art so that it remains sustainable amidst current developments.